Property cycles in Dublin - the anatomy of boom and slump in the industrial and office property sectors - MacLaran, Andrew; MacLaran, Morag; Malone, Patrick (Economic & Social Studies, 1987)
The property development process is the means by which built space is created to accommodate the variety of urban functions. The paper examines the existence of boom-slump cycles in the industrial and office property development sectors and their relationship to Irish macroeconomic trends. The consequences of boom and slump are examined with respect to the construction sector and in relation to Dublin's built environment.
Keywords: Property market - Ireland; Property development - Dublin